Towards a service-based internet. ServiceWave 2010 workshops International workshops, OCS, EMSOA, SMART, and EDBPM 2010, Ghent, Belgium, December 13-15, 2010, revised selected papers - Cezon, Michel; Wolfsthal, Yaron; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of four workshops held in conjunction with the Third European Conference, ServiceWave 2010, held in Ghent, Belgium, in December 2010. The book includes 23 reviewed papers from four workshops that were selected from eight high-quality workshop session proposals. They represent diverse aspects of the theory and practice of service computing, ranging from service engineering to service infrastructures. The workshops are: First Workshop on Optimising Cloud Services (OCS 2010), International Workshop on Emergency Management through Service-Oriented Architectures (EMSOA 2010), First International Workshop on Service Modelling and Representation Techniques (SMART 2010), and From Event-Driven Business Process Management to Ubiquitous Complex Event Processing (EDBPM 2010).
Electronic reproduction.
Keywords: Electronic books; Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Artificial intelligence; Information Systems